Modulation of imidazoline I(2) binding sites by CR4056 relieves postoperative hyperalgesia in male and female rats - Lanza, Marco (Blackwell Publishing Ltd, 2014)
BACKGROUND AND PURPOSE: CR4056 is a novel imidazoline-2 (I(2)) ligand exhibiting potent analgesic activity in animal models of pain. In this study, we investigated the effects of CR4056 in a well-established model of postoperative pain where rats develop hyperalgesia in the injured hind paw. EXPERIMENTAL APPROACH: By measuring paw withdrawal threshold to mechanical pressure, we studied the pharmacology of CR4056, potential sex differences in pain perception and response to treatment, and the pharmacodynamic interaction of CR4056 with morphine. KEY RESULTS: Oral CR4056 and subcutaneous morphine dose-dependently reversed the hyperalgesic response. Analgesic effects of CR4056 were completely suppressed by the non-selective imidazoline I(2)/α(2)-adrenoceptor antagonist idazoxan, were partially reduced (∼30%; P < 0.05) by the selective α(2)-adrenoceptor antagonist yohimbine, but were not influenced by the non-selective I(1)/α(2)-adrenoceptor antagonist efaroxan or by the μ opioid receptor antagonist naloxone. We found no differences in responses to CR4056 or morphine between male and female rats. However, females had a lower pain threshold than males, and needed lower doses of drugs to reach a significant analgesia. When CR4056 and morphine were combined, their median effective doses were lower than expected for additive effects, both in males and in females. Isobolographic analysis confirmed a synergism between CR4056 and morphine. CONCLUSIONS AND IMPLICATIONS: CR4056 is a novel pharmacological agent under development for postoperative pain both as stand-alone treatment and in association with morphine. CR4056 has successfully completed Phase I studies for tolerability and pharmacokinetics in healthy volunteers, and is currently entering the first proof-of-concept study in patients.